2012
DOI: 10.1186/1752-153x-6-s2-s10
|View full text |Cite
|
Sign up to set email alerts
|

XPS characterization of (copper-based) coloured stains formed on limestone surfaces of outdoor Roman monuments

Abstract: Limestone basements holding bronzes or other copper alloys artefacts such as sculptures, decorations and dedicatory inscriptions are frequently met both in modern and ancient monuments. In outdoor conditions, such a combination implies the corrosion products of the copper based alloy, directly exposed to rainwater, will be drained off and migrate through the porous surfaces, forming stains of different colours and intensities, finally causing the limestone structures to deteriorate.In this work we have analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The shifting of Zr 3d3/2 and Zr 3d5/2 peaks toward lower binding energies (approximately 183.8 and 181.5 eV, respectively) indicated the possible occurrence of chemisorption due to surface complexation between Cu(II) and zirconium hydroxide (ZrOH + Cu 2+ = ZrOCu + + H + ). The absence of any prominent peak throughout the Cu2p region (binding energy 925.0‐960.0 eV) before adsorption of Cu(II) and the appearance of new Cu2p peaks (2p 3/2 and 2p 1/2 , due to spin‐orbit splitting for the orbital including I > 1) separated by about 20 eV (at 932.98 and 952.23 eV) after adsorption of Cu(II) are consistent with previously reported results . This phenomenon is attributed to the adsorption of Cu(II) onto the ZO@AB .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The shifting of Zr 3d3/2 and Zr 3d5/2 peaks toward lower binding energies (approximately 183.8 and 181.5 eV, respectively) indicated the possible occurrence of chemisorption due to surface complexation between Cu(II) and zirconium hydroxide (ZrOH + Cu 2+ = ZrOCu + + H + ). The absence of any prominent peak throughout the Cu2p region (binding energy 925.0‐960.0 eV) before adsorption of Cu(II) and the appearance of new Cu2p peaks (2p 3/2 and 2p 1/2 , due to spin‐orbit splitting for the orbital including I > 1) separated by about 20 eV (at 932.98 and 952.23 eV) after adsorption of Cu(II) are consistent with previously reported results . This phenomenon is attributed to the adsorption of Cu(II) onto the ZO@AB .…”
Section: Resultssupporting
confidence: 91%
“…Ideally, Accordingly, the adsorption capacities of ZO@AB for Cu(II) during successive sorption/regeneration cycles were studied as charted in reported results. 36 This phenomenon is attributed to the adsorption of Cu(II) onto the ZO@AB. 37 Further, the Ca2p spectra of ZO@AB acquired before and after adsorption of Cu(II) are displayed in Figure 2C.…”
Section: Regeneration Studiesmentioning
confidence: 99%
“…3. b-d) and the quantification analysis are presented in Table 1. It is commonly recognized that the Cu 2p 3/2 photoelectron peak around of 933.3-934.0 eV with shake-up satellite is due to the CuO (or Cu 2+ ), while many researchers identified that the Cu 2p 3/2 photoelectron peak at around of 932.5-932.8 eV is from the tetrahedral Cu + with its counterpart peak from octahedral Cu + located below the tetrahedral one [15,[28][29][30][31][32][33][34][35][36]. From Table 1, the octahedral and tetrahedral Cu + as well as the octahedral and paramagnetic Cu 2+ oxidation states are detected with the tetrahedral Cu + being the most prominent.…”
Section: Synchrotron Radiation Xps Studymentioning
confidence: 99%
“…Generally, the corrosion products of metals are coloured, and thus their precipitation has often the negative consequence of staining the stone: [2] copper products form green, bluish or yellowish stains; iron products give the well-known rusty colour; divalent lead oxides and minium give red stains, whereas lead dioxide contributes to the blackening of the stains. [3] The copresence of different metals may give rise to the formation of mixed compounds with unusual colours whose composition is more difficult to be interpreted (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%